Regulated Expression and Function of the Somatodendritic Catecholamine Neurotransmitter Transporters - Shigeo Kitayama; Chiharu Sogawa (Elsevier, 2005)
Termination of neurotransmission at catecholaminergic synapses is well documented by the transporters for dopamine and norepinephrine, members of the Na+/Cl−-dependent neurotransmitter transporter family, which accumulates released transmitters within their nerve endings, respectively. Although somatodendritic expression of the transporters and the effects of cocaine and amphetamine on those have been reported, their role is still obscure. Recent findings of the transporter function as an ion channel and/or its reverse transport property provide a clue to identify the role of these transporters in the somatodendrites and their consequential interaction with uptake inhibitors. Differences in ionic environment and maturity of the release machinery in the somatodendrites at developmental stages influence the transporter functions, resulting in the formation of both positive and negative feedback loop of catecholaminergic neurons. Keywords:: dopamine, norepinephrine, uptake inhibitor, reverse transport, chloride current